USING PERSONAL JOURNAL TO IMPROVE WRITING ABILITY IN RECOUNT TEXT - Ali Syahban Amir (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
The application of learning through the use of  personal journal is related to the learning of the "Recount text", where this text leads to the process of retelling about experiences in the past to provide information or to entertain the reader. Based on several previous researchers, it has been suggested that learning writing through a personal journal can become a habit that has an impact on increasing students' interest in writing. The application of this learning is aimed to find an increase in learning ability of writing skills, especially in writing "Recount text". This research is a quasi-experimental design with involving experiment 1 and 2. The experiment 1 was taught with the use of a personal journal while the experiment 2 was taught with the learning as applied by the teacher. Data collection for student learning outcomes is done by giving a test of learning outcomes after being treated in each group. The findings in this study indicate that there is an increase in students' writing Recount through the use of personal journal. The mean score in the pre-test of the Experiment 1 there was an increase of 11.13%. In the experimental 2 there was an increase of 10.16%. This proves that the use of personal journal is more effective.